Women and Local Peacebuilding Initiatives in Nigeria: Everyday Agency, Bridge-Building, and the Politics of Survival - Fagbewesa, Esther Olapeju; Oyadiran, Kehinde; Bodunrin, Titilayo A.; Gbadeyan, Olawale James (NIU Journal of Legal Studies, 2026)
This article examines women’s local peacebuilding initiatives in Nigeria through a qualitative evidence synthesis of published studies, with particular attention to the insurgency-affected northeast and to broader women-led civic mobilisation in fragile and conflict-affected settings. It argues that women’s peacebuilding in Nigeria is best understood not as a peripheral humanitarian supplement to formal peace processes, but as a core form of everyday political agency that sustains communities, repairs fractured social relations, and challenges gendered exclusions embedded in both state security practice and orthodox peacebuilding. Drawing on feminist peacebuilding theory, the local turn in peacebuilding, and the literature on everyday peace, the article analyses how women act as interfaith bridge-builders, livelihood organisers, informal mediators, rescuers, reintegration brokers, and movement leaders. The analysis is anchored on recent interview-based study of women peacebuilders in northeastern Nigeria and is extended through Nigeria-focused scholarship on women-led civil society organisations, displacement, countering violent extremism, women’s organising under fragility, and the localisation of the Women, Peace and Security agenda. The findings are organised around five themes: bridge-building across religious and communal divides; care and livelihoods as material peace infrastructure; informal mediation and reintegration; grassroots-to-public advocacy; and the structural limits imposed by militarisation, securitisation, and weak localisation of gender policy. The study concludes that women’s local peacebuilding in Nigeria is transformative but overburdened: it expands women’s authority and social influence, yet continues to operate without adequate institutional recognition, resourcing, or protection. Sustainable peace in Nigeria will require moving beyond symbolic inclusion toward an architecture that centers women’s local knowledge, redistributes decision-making power, and treats community-based peace labor as a fundamental pillar of national peacebuilding. Keywords: Women; Local Peacebuilding; Nigeria; Everyday Peace; Feminist Peacebuilding; Women, Peace and Security; Boko Haram; Qualitative Evidence Synthesis.